Implementasi Teknologi Augmented Reality Menggunakan Magic Book Sebagai Media Pemasaran Produk Berbasis Android - Andhika Alfino Abbas; Tajuddin Abdillah; Rampi Yusuf (Diffusion: Journal of Systems and Information Technology, 2021)
This study is conducted based on the problem faced by the owner of the Nurhayati Shop. motivated by the obstacles that are often experienced by the owner nurhayati shop. The 2D Tupperware catalog used by Nurhayati Shop becomes the core problem in serving the customers due to the inefficient time and product description. This study applies Multimedia Life Cycle (MDLC) as the method. The result shows that augmented reality technology integrated into a magic book can be used as the marketing media with android-base. Technology helps the seller in promoting the product throught the android that changes the object into 3D. Besides, it helps the buyer to have an effective time to choose the product.